2020
DOI: 10.21203/rs.3.rs-105866/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into the cultured bacterial fraction of corals

Abstract: Bacteria associated with coral hosts are diverse and abundant, with recent studies suggesting involvement of these symbionts in host resilience to anthropogenic stress. Despite the putative importance of bacteria, the work dedicated to culturing coral-associated bacteria has received little attention. Combining published and unpublished data, here we report a comprehensive overview of the diversity and function of culturable, coral-associated bacteria. A total of 3055 isolates from 52 studies were considered b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 80 publications
3
25
0
Order By: Relevance
“…The use of culture-dependent and independent methods showed that these approaches provided complementary results regarding the presence and enzymatic activity of specific CAM. Interestingly, the genera Arthrobacter, Acinetobacter, Raoutella, Virgibacillus, and Cellulomonas were detected in Ma only through culture-dependent methods, while the most abundant genus detected by molecular tools, Mycobacterium, was not isolated from Ma samples, likely due to culture media and strategy limitations [31]. In addition, Exiguobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of culture-dependent and independent methods showed that these approaches provided complementary results regarding the presence and enzymatic activity of specific CAM. Interestingly, the genera Arthrobacter, Acinetobacter, Raoutella, Virgibacillus, and Cellulomonas were detected in Ma only through culture-dependent methods, while the most abundant genus detected by molecular tools, Mycobacterium, was not isolated from Ma samples, likely due to culture media and strategy limitations [31]. In addition, Exiguobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, microbial strains isolated from marine ecosystems have been reported producing several types of substances with protective properties against viruses, bacteria, fungi, and tumors, as well as enzymes of industrial interest [24][25][26][27]. Among marine ecosystems, coral reefs have been highlighted as a promising target for bioprospecting for natural products, due to the diversity of macro-and micro-organisms [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…R e v i e w s 0123456789();: immobilization of microbial cells and/or slowing their temporal release through attachment to biocompatible carriers, as well as bioencapsulation in prey or uptake through heterotrophic feeding 54,184 . Although existing genetic engineering techniques are easily applied to bacterial isolates derived from corals, they should be restricted to a laboratory context, as the effects that such altered genetic variants could exhibit in the highly complex and diverse coral reef environment (for example, interaction with pathogens) are unknown [185][186][187] . Accordingly, coral microbiome manipulative approaches at reef sites should focus on utilization of microbes (bacteria) from the native environment.…”
Section: Nature Reviews | Earth and Environmentmentioning
confidence: 99%
“…Finally, culture-based approaches will allow source tracking of microbial partners, and a rapid boom in microfluidics-based approaches now enables isolation of the unculturable bacteria ( 21 ). In this respect, a central repository of coral-isolated microbes has been proposed with the goal of development of coral probiotics, but currently no databases exist for coral-associated bacterial metabolomes ( 22 ). The marine environment is a significant source of the coral microbiome.…”
Section: Omics Approaches In Holobiont Sciencementioning
confidence: 99%